Analysis of the effectiveness of the "Environmental Protection Tax Law" from the tax amount of atmospheric pollutants. Issue 1 (February 2021) - Zhang, Yu; Wu, Peng; Shan, Baoguo; Tang, Wei; Wang, Chengjie; Tan, Qingkun; Chen, Bo; Xiong, Ke
Abstract: China's atmospheric pollutants are mainly sulphur dioxide and nitrogen oxides, and the "Environmental Protection Tax Law of the People's Republic of China" stipulates relevant regulations on the collection of environmental protection taxes on atmospheric pollutant emissions. In this paper, by calculating the equivalent pollutant emissions of various terminal energy sources, according to the environmental protection tax items and tax standards, the environmental protection tax payable for various terminal energy sources is obtained. By comparing the environmental protection tax amounts of various terminal energy sources, it is found that the current environmental protection tax collection standards are too low, which can neither compensate for the economic and environmental losses caused by pollutants emitted by fossil energy sources, nor improve the price advantage of clean energy.